Joint Source and Relay Optimization for Distributed MIMO Relay System - Toding, Apriana; Khandaker, Muhammad; Rong, Yue (IEEE, 2011)
In this paper, we develop the optimal transmit beamforming vector and the relay amplifying factors for a multiple-input multiple-output (MIMO) relay communication system with distributed relay nodes. Using the optimal beamforming vector, an iterative joint source and relay beamforming algorithm is developed to minimize the mean-squared error (MSE) of the signal waveform estimation. Numerical simulations are carried out to demonstrate the performance of the proposed joint source and relay beamforming algorithm.